An Evaluation of Educational Iranian Papers on the Application of EvidenceBased Medicine - Shahrzad Saravani; Maryam Yazdandoost; Hamed Basir-Ghafouri (Kerman University of Medical Sciences, 2015)
Background & Objective: Nearly two decades have passed since the establishment of evidencebased medicine (EBM) EBM is of great importance due to its ability to fill the information gap between medical research and clinical practice The aim of the present study was to evaluate the existing evidence of the application of EBM in published Iranian educational papers   Methods: This is a systematic review of Iranian papers published in both Iranian and international journals The results were reviewed by two researchers separately to assess the inclusion and exclusion criteria and evaluate the level of evidence We used the Best Evidence Medical Education (BEME) guideline for conducting the systematic review and the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) flowchart to present the selection process In addition the Medical Education Research Quality Index (MERSQI) was used for the evaluation of the quality of the studies   Results: EBM was used in 11 fields which can be categorized as the 4 clinical educational research and policymaking groups The educational group consisted of 3 domains of holding a journal club case discussions and teaching and learning Only 6 studies were found to report the effect of education on the application of evidencebased medicine The evaluation of their quality showed average quality   Conclusion: Although there are a limited number of studies on the effect of education on EBM application they present satisfactory and average quality evidence Despite the existence of various educational courses on EBM in Iran no high level and high quality evidence exists to show the effectiveness of education on knowledge attitude practice and behavior of healthcare professionals especially in the longterm Thus the designing and performing of high quality research is required in this field